Barricading the Border: COVID-19 and the Exclusion of Asylum Seekers at the U.S. Southern Border - Gilman, Denise (Frontiers in Human Dynamics, 2020)
What years of deterrence efforts and restrictions on asylum did not achieve to block the U.S. southern border to asylum seekers, the Trump Administration has now accomplished using the COVID-19 pandemic as justification. New measures exclude asylum seekers from U.S. territory, thereby effectively obliterating the U.S. asylum program, which had promised refugee protection in the form of asylum to eligible migrants who reach the United States. In some cases, the policies adopted during the COVID-19 pandemic harden impediments to asylum already in place or implement restrictions that had been proposed but could only now be adopted. In others, the policies could never have been imagined before the pandemic. Overall, the force of these measures in dismantling the asylum system cannot be overemphasized. Once adopted, using an emergency rationale based on the pandemic, these policies are likely to become extremely difficult to reverse. This is particularly true where the restrictions exclude asylum seekers from the physical space of the United States. This article will thus explore two modes of physical exclusion taking place at the U.S. southern border during the COVID-19 pandemic: 1) indefinitely trapping in Mexico those asylum seekers who are subject to the so-called Migrant Protection Protocols; and 2) immediate expulsions of asylum seekers arriving at the southern border pursuant to purported public health guidance issued by the U.S. Centers for Disease Control and Prevention.